UJI ANALGESIK KOMBINASI EKSTRAK ETANOL DAUN BLIMBING WULUH (Averrhoa bilimbi L.) DAN DAUN KELOR (Moringae Oliferae L.) PADA MENCIT JANTAN GALUR Swiss Webster - Devi Amalila; Galih Samodra; Adita Silvia Febriana (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2021)
Analgesic drugs are used to reduce and relieve pain without loss of consciousness. The plants used as analgesics were Moringa leaves (Moringae Oliferae L.) and starfruit leaves (Averrhoa Bilimbi L.), because these two plants showed the presence of compounds such as flavonoids, alkaloids, saponins, and tannins. The aim of the study was to determine the analgesic effect. In Moringa leaf and star fruit leaf male Swiss Webster mice, the combined dose of 2:2 and 800 mg of Moringa oleifera extract and 1000 mg of star fruit extract were reduced in each rat. The method used to test the analgesic activity is the hot plate method. The responses of mice before administration and 0, 15, 30, 45, and 60 minutes after administration were observed, and the data were analyzed by ANOVA and LSD tests. Moringa leaf extract and belimbing wuluh leaf extract at a combined dose of 1:1, 2:2, 2:1 had analgesic effect on male Swiss Webster strain male mice. The three best combinations that gave analgesic effect were at a combination of 2:2 doses and 800mg and 1000mg doses, the average tensile protection results obtained were 0%, 65; 06%, 13; 65%, -15.29%, 18; 33%.